2009
DOI: 10.1155/2009/398767
|View full text |Cite
|
Sign up to set email alerts
|

Front-Loading Sputum Microscopy Services: An Opportunity to Optimise Smear-Based Case Detection of Tuberculosis in High Prevalence Countries

Abstract: Setting. Ethiopia, Nepal, Nigeria, and Yemen. Objective. To reduce the time to complete sputum microscopy. Design. Cross-sectional surveys enrolling 923 patients with chronic cough in the 4 countries and using similar protocols. Spot-morning-spot sputum specimens were collected. An additional sputum specimen (Xspot) was collected one hour after the first, and the yields of the first two or the three specimens collected as spot-morning-spot or spot-Xspot-morning were compared. Results. 216 patients had ≥ one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 8 publications
3
44
1
Order By: Relevance
“…It is relatively cheap, simple and identifies the most infectious cases. However, the requirement for repeated visits to submit specimens and receive results is associated with considerable diagnostic delay, work load and dropout of patients from the diagnostic process [4][5][6]. This study was designed to assess the yield of first spot double slides smears for the diagnosis of PTB in high TB setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is relatively cheap, simple and identifies the most infectious cases. However, the requirement for repeated visits to submit specimens and receive results is associated with considerable diagnostic delay, work load and dropout of patients from the diagnostic process [4][5][6]. This study was designed to assess the yield of first spot double slides smears for the diagnosis of PTB in high TB setting.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the value of three sputum smears showed that about 24% of PTB suspects failed to return after submitting the first spot specimen and 4.5% of these suspects were smear positives [7]. In addition, study carried out on front loading sputum microscopy services showed that ≥ 10% of patients failed to return for the second day of diagnosis [4]. Similarly, in the present study, among the 30 suspects who failed to return after submitting the first spot specimen, 6 (10%) were found to be smear-positives based on the results of the first day samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of great importance here are translational researches bothering on the use of stool for prompt diagnosis of pediatric TB (Cadmus et al, 2009), adaptation of the front loading smear microscopy (Ramsay et al, 2009), and the use of light emitting diode (LED) microscopes (Cuevas et al, 2011) to mention a few. These translational researches are urgently needed giving the advantages they may offer in combating TB in the continent.…”
Section: Operational Researchmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Based on the results of these studies, the WHO recommended that countries using a 2-day specimen collection strategy for TB diagnosis should consider moving to same-day sputum collection. 13 All of the studies that formed the basis of the WHO recommendation, however, are from trial settings [5][6][7][8][9][10][11][12] and not from routine programmatic settings. In addition, two studies conducted in tertiary care settings in India have provided conflicting results: one supported the same-day sputum collection strategy 9 while the other did not.…”
mentioning
confidence: 99%